Ability Emotional Intelligence, Attachment Models, and Reflective Functioning - Rosso, Anna Maria (Frontiers in Psychology, 2022)
Previous studies have reported that individual differences in ability emotional intelligence (EI) are associated with quality of attachment, showing that securely attached individuals perform better on Ability emotional intelligence tasks. However, these studies may, to some extent, be misleading because they relied on self-report measures of attachment security. Furthermore, to our knowledge, no study has yet investigated the relationship between ability EI and mentalization, operazionalized as reflective functioning (RF), although both EI and RF are assumed to promote psychological health and are significantly associated with interpersonal skills. In an attempt to overcome some of the limitations of the previous research, the current study investigated the relationships between Ability EI, attachment security, and mentalization measured via the Adult Attachment Interview (AAI). One hundred volunteer participants from a community population took part in the study. In the entire sample, ability EI correlated positively with Coherence of mind regarding attachment experiences, and negatively with hyperactivating attachment strategies. Significant positive associations were also found between RF and all ability EI scores but the “Managing emotions” branch. Since females showed significantly higher scores than males on ability EI and RF, separate analyses by gender were additionally performed. A positive association between Branch 3 “Understanding emotions”, RF, and Coherence of mind was found in the females. Hyperactivating attachment strategies correlated negatively with ability EI both in females and males. Unexpectedly, the “Insistence on lack of recall” scale (a marker of dismissing state of mind) was positively associated with Experiential EI in the female group.